2008
DOI: 10.2460/ajvr.69.7.900
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma iron concentration and gastric pH in captive adult bottlenose dolphins (Tursiops truncatus)

Abstract: Analysis of results reported here suggested that gastric pH may play an important role in iron absorption in dolphins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Whilst the presence of basal cells and erythrocytes (RBC) may be a sign of ulceration (Mitchell et al, 2008), basal cells were present in the gastric fluid where ulceration was absent on two occasions in the present study and were not seen in the gastric fluid where grade 4 ulceration was observed. RBC were found on only two occasions in this study, once in a sample taken by gastroscopy from a dolphin with grade 4 ulceration; and the other at an unknown ulcer severity where the gastric sample was collected through intubation.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Whilst the presence of basal cells and erythrocytes (RBC) may be a sign of ulceration (Mitchell et al, 2008), basal cells were present in the gastric fluid where ulceration was absent on two occasions in the present study and were not seen in the gastric fluid where grade 4 ulceration was observed. RBC were found on only two occasions in this study, once in a sample taken by gastroscopy from a dolphin with grade 4 ulceration; and the other at an unknown ulcer severity where the gastric sample was collected through intubation.…”
Section: Discussioncontrasting
confidence: 47%
“…Whilst the presence of basal cells and erythrocytes (RBC) may be a sign of ulceration (Mitchell et al, 2008) The mean pH of the gastric samples across all ulcer grades in this study was within the normal range for fasted, clinically healthy dolphins…”
Section: Discussionmentioning
confidence: 51%
“…Ascorbic acid enhances the absorption of dietary iron, 32 and high-quality fish contain adequate amounts of iron, thereby eliminating the need for administration of supplemental iron. Also, a recent study 33 revealed that gastric pH may play a role in iron absorption and maintenance of plasma iron concentrations in bottlenose dolphins. Thus, treatment with antacids to increase gastric pH may reduce iron absorption in dolphins with iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Given the four-chambered stomach morphology of odontocetes, it is difficult to measure the real pH value of the digestion fluids in the forestomach ( Mitchell et al, 2008 ). Digestion fluids are produced in the main stomach and flow potentially randomly as a reflux into the forestomach.…”
Section: Discussionmentioning
confidence: 99%